Application of Evidence in the Primary Prevention of Type 2 Diabetes Mellitus in Addressing the Epidemic in Papua New Guinea - Leslie Bahn Kawa (Emerging Trends in Disease and Health Research Vol. 9, 2022)
Type 2 diabetes is rising at an alarming rate in Papua New Guinea and the country has no policy to address this epidemic. Evidence available in the primary prevention of type 2 diabetes is not widely known to be applied in a fractured healthcare system among the high-risk population. The objective of this literature review is to assess all available evidence in the primary prevention of type 2 diabetes mellitus and to suggest the integration and the application of the relevant evidence in the Papua New Guinean response to the type 2 diabetes epidemic under a clear policy. A literature review was conducted to analyze the available evidence in the primary prevention of type 2 diabetes in the pre-diabetic population. The findings demonstrated that the primary prevention researches on lifestyle change, and the use of metformin among the prediabetes individuals have reduced the occurrence of overt type 2 diabetes. It is, therefore, possible to use these evidences to address the type 2 diabetes epidemic in Papua New Guinea, to be driven by a non -communicable disease policy.